Bond Strength of Rectangular CFSST Columns after Exposed to Elevated Temperature - Anandapadmanaban K.; A. S. Santhi (Civil Engineering Journal, 2024)
This article investigates the bond- behavior of Rectangular Concrete-filled stainless-steel tubular (RCFSST) columns under post-fire conditions. The main objective of this research was to obtain τ-s relationship of RCFSST columns under the combined effects of high temperature and concrete age. A total of sixteen specimens, including four reference specimens, were tested with different parameters, namely: i) temperature (600 °C, 800 °C & 1000 °C) ii) different concrete ages (30 days, 60 days, 90 days & 180 days). Analyzing the τ-s curves of the test specimens, chemical adhesion and micro-locking were the principal forces contributing to bond strength at lower concrete ages under post-fire conditions. At a higher concrete age, RCFSST specimens displayed a longer curve after the inflection point, indicating the contribution of macro-locking forces in amplifying the bond-strength. Five distinct curve types were found from the experiments. Type 1 curves with three stages, i) initial linear, ii) non-linear, and ii) final linear stage, had a higher frequency among the other types. For 90-day cured specimens, a decline in bond strength was observed at higher temperatures, but for 180 days cured specimens, a significant rise was seen under post-fire conditions. A new set of τ-s relations for RCFSST columns with different concrete ages under post-fire was established. Doi: 10.28991/CEJ-2024-010-03-019 Full Text: PDF